Noninvasive Tests in the Assessment of NASH and NAFLD Fibrosis: Now and Into the Future - Adams, Leon A.; Chan, Wah-Kheong (Seminars in Liver Disease, 2020)
Noninvasive serum and imaging methods offer accessible, accurate, and safe assessment of fibrosis severity in nonalcoholic fatty liver disease. In contrast, current serum and imaging methods for the prediction of nonalcoholic steatohepatitis are not sufficiently accurate for routine clinical use. Serum fibrosis markers that incorporate direct measures of fibrogenesis (for example, hyaluronic acid) or fibrinolysis are generally more accurate than biomarkers not incorporating direct measures of fibrogenesis. Elastography methods are more accurate than serum markers for fibrosis assessment and particularly for the determination of cirrhosis, but have a significant failure and/or unreliability rate in obese individuals. To overcome this, combining serum and elastography methods in a sequential manner minimizes indeterminate results and maintains accuracy. The accuracy of current noninvasive methods for monitoring fibrosis response to treatment are limited; however, new tools derived from “omic” methodologies offer promise for the future.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; elastography; serum biomarkers